Evaluasi Pengalaman Pengguna Aplikasi SIMARIS UPN “Veteran” Jawa Timur Menggunakan Metode UEQ - Anisa Rahma Salsabila; Tri Lathif Mardi Suryanto; Eristya Maya Safitri (STMIK Budi Darma, 2022)
The implementation of information and communication technology in a university is increasing according to the needs of each university. Research and community service activity carried out by lecturers at UPN